Estimating monetary damages from flooding in the United States under a changing climate. Issue 3 (3rd April 2013) - Wobus, C.; Lawson, M.; Jones, R.; Smith, J.; Martinich, J.
Abstract Extreme precipitation events are likely to become more frequent and more extreme under a changing climate. It follows that monetary damages from flooding would also increase relative to baseline, yet this relationship has not been quantified at the scale of the entire United States. In this paper, we quantify how climate change could affect monetary damages from flooding in the coterminous United States. With publicly available historical flooding and precipitation data, we estimate region‐specific logistic regression models of the probability that severely damaging floods will occur under baseline conditions. We then use future precipitation projections driven by climate model outputs to estimate the probability that damaging floods could occur under a 'business as usual' climate change scenario. Our results project an increase in monetary damages from flooding in nearly all regions of the United States and a total increase in damages by the end of century of approximately 30% (assuming no change in built infrastructure or values). However, these changes vary between regions due to differences in the mechanisms driving flooding and general circulation model precipitation projections.